"Nothing Hurts Less Than Being Dead": Psychological Pain in Case Descriptions of Psychiatric Euthanasia and Assisted Suicide from the Netherlands: « Rien ne fait moins mal qu'être mort »: La douleur psychologique dans les descriptions de cas d'euthanasie et de suicide assisté psychiatrique aux Pays-Bas. (September 2020) - Lengvenyte, Aiste; Strumila, Robertas; Courtet, Philippe; Kim, Scott Y. H.; Olié, Emilie
Objectives: Euthanasia and assisted suicide (EAS) of individuals with mental disorders is a growing practice in several countries, including the Netherlands. Here, we aimed to identify the most frequent dimensions of and associated factors to psychological pain, which has been associated with suicidality, in individuals undergoing psychiatric EAS. Methods: An exploratory retrospective content analysis of the English translation of 66 digital case records of individuals who died by EAS in the Netherlands between 2011 and 2014 was performed. Nine standard psychological pain dimensions (irreversibility, loss of control, emptiness, emotional flooding, freezing, social distancing, narcissistic wounds, confusion, and self-estrangement), illness, and sociodemographic variables were evaluated by 2 independent raters using a premade data abstraction form (Kohen κ > 0.8 in all cases). Results: The mean number of dimensions was 4.64 ± 1.20 (median = 5), out of 9. The most frequent dimensions were irreversibility, loss of control, emptiness, and emotional flooding, in decreasing order. Past treatment refusal and the mention of social connections in case descriptions were related to the higher number of psychological pain dimensions (4.89 ± 1.24 vs. 4.31 ± 1.07, P = 0.03 and 5.05 ± 1.17 vs. 4.43 ± 1.17, P = 0.03, respectively). Emotional flooding was the only dimension specifically associated with specific psychiatric conditions, namely posttraumatic phenomena and personality disorders. Conclusions: Numerous psychological pain dimensions were detected in case descriptions of individuals who underwent EAS before the procedure. Subjective nature of the study precludes definite conclusions but suggest that future studies should explore psychological pain and the role of interventions targeting it in patients requesting EAS.